Benefits of heat-killed Lactobacillus acidophilus on growth performance, nutrient digestibility, antioxidant status, immunity, and cecal microbiota of rabbits - Xia, Miao; LI, Chong; Wu, Diange; Wu, Fengyang; Kong, Lingchang; Jia, Zifan; Han, Wenxiao; Chen, Saijuan; Fang, Wei; Liu, Yajuan; Chen, Baojiang (Frontiers in Veterinary Science, 2024)
This study aimed to investigate the impact of heat-killed Lactobacillus acidophilus (L. acidophilus, LA) -a deactivated probiotic on the growth performance, digestibility, antioxidant status, immunity and cecal microbiota of rabbits. Two hundred weaned Hyla rabbits were randomly allocated into five equal groups (CON, L200, L400, L600, and L800). The rabbits were fed basal diets supplemented with 0, 200, 400, 600, and 800 mg/kg of heat-killed LA, respectively. Results revealed a significant reduction in the feed-to-gain ratio (F/G) in the L600 and L800 groups (p < 0.05).The L800 group exhibited significantly higher apparent digestibility of CF and CP (p < 0.05).Regarding digestive enzyme activities, enhanced trypsin and fibrinase activities were observed in the L600 and L800 groups (p < 0.05). Concerning the regulation of the body's antioxidant status, the L800 group demonstrated elevated levels of superoxide dismutase (SOD) and total antioxidant capacity (T-AOC) in both serum and ileal tissue (p < 0.05). In terms of immune capacity modulation, serum tumor necrosis factor-α (TNF-α) levels were significantly lower in the L600 and L800 groups (p < 0.05), while immunoglobulin A (IgA) and immunoglobulin M (IgM) levels were higher (p < 0.05).Additionally, the L800 group exhibited a substantial increase in secretory immunoglobulin A (SIgA) levels in the intestinal mucosa (p < 0.05). In comparison to the CON group, the L800 group exhibited a significant increase in the relative abundance of Phascolarctobacterium and Alistipes in the cecum (p < 0.05). Phascolarctobacterium demonstrated a positive correlation with SIgA (p < 0.05), IgM (p < 0.01), and Glutathione peroxidase (GSH-Px) (p < 0.05), while displaying a negative correlation with TNF-α levels (p < 0.05). Concurrently, Alistipes exhibited positive correlations with IgA (p < 0.05), IgM (p < 0.05), SIgA (p < 0.01), GSH-Px (p < 0.05), SOD (p < 0.05), and T-AOC (p < 0.01), and a negative correlation with TNFα (p < 0.05). In conclusion, the dietary incorporation of 600 mg/kg and 800 mg/kg of heat-killed LA positively influenced the growth performance, nutrient digestibility, antioxidant status, immune capacity and cecal microbiota of rabbits. This highlights the potential benefits of utilizing heat-killed probiotics in animal nutrition.